The Cartesian Political Subject - Daniil Vashkevich (Ars & Humanitas)
René Descartes is usually presented in the history of philosophy as a thinker who established new foundations for the European scientific project. However, the political aspect of the Cartesian method is often overlooked. What were the socio-political reasons for Descartes’ turn to the cogito? Does the cogito enter into a certain contradiction when it transfers the foundation to God? And what does this dialectical play of foundations mean for the political? To answer these and other questions, this article conducts a comparative analysis of the views of René Descartes and Thomas Hobbes. It is known that both were adherents of the Cartesian method, which would suggest similarities in their political conclusions. However, this article argues that despite the similarity in their approaches, they arrive at different solutions for the dialectical resolution of the contradiction embedded in the Cartesian method.